Chronic Diarrhea in a Drinker: A Breakthrough Case of Pellagra in the US South. (July 2020) - Mills, Krystal; Akintayo, Oluwole; Egbosiuba, Linda; Dadzie, Salome; Skyles, Adrina; Jang, Kudo; Fatima, Shaheen; Fas, Norberto
The triad of diarrhea, dementia, and dermatitis constitutes the clinical diagnosis of pellagra. However, most reported cases of pellagra have occurred without all components of the triad. Pellagra was declared eradicated in the United States after an outbreak in the 1920s, and is now considered to be an exceedingly rare diagnosis in developed countries. In this article, we present a case of a 56-year-old man who presented with a significant history of alcohol use and chronic diarrhea. Pellagra was clinically diagnosed based on the triad of diarrhea, cognitive dysfunction, and dermatitis in this malnourished, alcoholic patient. The patient was treated and clinically improved with resolution of his diarrhea and cognitive dysfunction.